Melitaia in Achaia Phthiotis: some first glances of an ancient city through a recent lidar survey - Rönnlund, Robin (Journal of Greek Archaeology, 2025)
The archaeological site of Melitaia is located in the administrative region of Sterea Ellada, approximately 16km north of the regional capital of Lamia and just east of the eponymous village (formerly Avaritsa). The site occupies a scenic spot overlooking the eastern half of the large plateau of Domokos – a fertile and well-watered hill-land separating the vast Thessalian plain to the north and the Valley of Spercheios to the south.